Exploring South African Perspectives On Husbands Adopting Their Wife’s Surname In Marriage: The Case Of Or Tambo District Municipality In The Eastern Cape Province - Kundlwana, Babalo; Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
Background: Surname practices in South Africa are deeply rooted in African cultural traditions, Christian belief systems and patrilineal kinship structures. Recent legal developments, particularly the Constitutional Court ruling allowing husbands to adopt their wife’s surname, have introduced a new dynamic into marital identity formation. However, limited research has examined how South Africans understand and interpret this shift, especially in communities where cultural norms remain strong. Aim: To explore South Africans’ views and opinions on men taking their wife’s surname within the context of legal rights, African cultural traditions, and Christian beliefs. Study setting: The research was conducted in the OR Tambo District Municipality in the Eastern Cape Province of South Africa, a region characterised by strong traditional practices, rural-urban diversity, and widespread Christian adherence. Methods: The study adopted a qualitative research design grounded in the interpretivist paradigm. Nineteen participants were selected through purposive and snowball sampling. Data were collected using an online semi-structured interview guide and analysed thematically following Braun and Clarke’s (2006) approach. Trustworthiness was ensured through credibility, dependability, transferability and confirmability measures. Results: Findings revealed high legal awareness of the recent ruling, yet acceptance of the practice remained limited. Most participants perceived husband-to-wife surname adoption as contradictory to African patrilineal traditions, ancestral lineage systems and Christian interpretations of marital headship. While a minority supported personal choice, emphasising equality and autonomy, many respondents particularly older and rural participants believed the practice should be discouraged. Generational and spatial differences were evident, with younger and urban respondents demonstrating more openness. Conclusion: Despite legal reform, cultural and religious frameworks continue to shape resistance to husbands adopting their wife’s surname. Identity practices remain rooted in ancestral continuity and theological understandings of family structure. The gradual emergence of acceptance, particularly among younger participants, suggests evolving cultural ecologies influenced by modern rights-based discourses. Contribution: This study provides empirical insight into an understudied socio-legal issue in South Africa and contributes to ecohumanist scholarship by illuminating how naming practices reflect the interplay between individual autonomy, tradition, spirituality and communal identity. The findings highlight the importance of culturally sensitive policymaking and the need for inclusive dialogue with traditional and religious leaders.